The Protestant Ethic and Work: Micro Evidence from Contemporary Germany - Jörg L. Spenkuch (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Few theories in the social sciences have gained more widespread acceptance than Max Weber's The Protestant Ethic and the Spirit of Capitalism - despite a lack of conclusive empirical evidence. At the core of Weber's theory lies a connection between Protestantism and attitudes toward work. Using micro-data from contemporary Germany, this paper investigates the impact of Protestantism on economic outcomes and whether any such connection still exists. To break the endogeneity in religious affiliation the paper exploits the fact that the geographic distribution of Catholics and Protestants is an artifact of a provision in the Peace of Augsburg in 1555. Reduced form and instrumental variable estimates indicate that, even today, Protestantism leads to higher earnings through increased hours of work, and substantially more self-employment. Institutional factors, or differences in human capital acquisition cannot account for this effect. Instead, the data point to an explanation based on individual values akin to a Protestant Ethic.
Keywords: 330; Protestantismus; Arbeitsethik; Einkommen; Selbstständige; Wirtschaftssoziologie; Deutschland